Novel construction of carbon nanofiber/CuCrO2 composite for selective determination of 4-nitrophenol in environmental samples and for supercapacitor application. Issue 26 (28th April 2021) - Sakthinathan, Subramanian; Rajakumaran, Ramachandran; Keyan, Arjunan Karthi; Yu, Chung-Lun; Wu, Chia-Fang; Vinothini, Sivaramakrishnan; Chen, Shen-Ming; Chiu, Te-Wei
Abstract : A simple hydrothermal process has been used to prepare a carbon nanofiber/copper chromium dioxide (CNF/CuCrO2 ) composite for the selective detection of 4-nitrophenol (4-NP) and supercapacitor applications. Abstract : A simple hydrothermal process has been used to prepare a carbon nanofiber/copper chromium dioxide (CNF/CuCrO2 ) composite for the selective detection of 4-nitrophenol (4-NP) and supercapacitor applications. The electrochemical sensor was developed with a glassy carbon electrode (GCE) modified with the CNF/CuCrO2 composite by the drop-casting method. The structural formation of the prepared materials was confirmed by infrared spectroscopy, electrochemical impedance spectroscopy, Raman spectroscopy, scanning electron microscopy, X-ray diffraction, and transmission electron microscopy. To investigate the electrochemical efficiency of the electrode, various electroanalytical techniques, namely, differential pulse voltammetry (DPV), cyclic voltammetry (CV) and galvanostatic charge–discharge tests, were employed. The GCE/CNF/CuCrO2 modified electrode exhibited excellent electrocatalytic behavior for the detection of 4-NP under optimized conditions with a low detection limit (0.022 μM), long linear response range of 0.1–150 μM, and high sensitivity (20.02 μA μM −1 cm −2 ). The modified electrode was used for the detection of 4-NP in real samples with satisfactory results. In addition, the GCE/CNF/CuCrO2 electrode has advantages such as stability, reproducibility, repeatability, reliability, low cost, and practical application. The CNF/CuCrO2 composite coated Ni-foam electrodes also exhibited excellent supercapacitor efficiency, with a high specific capacitance of up to 159 F g −1 at a current density of 5 A g −1 and outstanding cycling stability. Hence, the CNF/CuCrO2 composite is a suitable material for 4-NP sensors and energy storage applications.